IDO1 Inhibition Reduces Immune Cell Exclusion Through Inducing Cell Migration While PD-1 Blockage Increases IL-6 and -8 Secretion From T Cells in Head and Neck Cancer - Sieviläinen, Meri; Saavalainen, Jordan; Adnan-Awad, Shady; Salo, Tuula; Al-Samadi, Ahmed (Frontiers in Immunology, 2022)
Background: Immune checkpoint inhibitors (ICIs), primarily anti-PD-1, are currently used to treat patients with recurrent or metastatic head and neck squamous cell carcinoma (HNSCC). However, only a minority of patients benefit from these costly therapies. Therefore, there is an unmet need to better understand the effect of ICIs on immune effector cells. This study aimed to investigate the effect of a PD-1 antibody and an IDO1 inhibitor on different lymphocyte populations (NK, CD4+, and CD8+ T cells) on migration, cytotoxicity, and cytokine release in the presence of HNSCC cells. Methods: Using a microfluidic chip, we injected HSC-3 cells (an oral tongue squamous cell carcinoma cell line) embedded in a human tumor-derived matrix “myogel/fibrin” together with NK, CD4+, and CD8+ T cells in separate channels. The two channels were connected with microchannels. The PD-1 antibody nivolumab and IDO1 inhibitor epacadostat were added to the microfluidic chips. Lymphocyte migration and cytotoxicity were examined under fluorescent microscopy and cytokine release was measured using a FirePlex Human Discovery Cytokines Immunoassay. Results: Epacadostat significantly increased the migration and infiltration of NK and CD4+ T cells, but not CD8+ T cells, towards the cancer cells. Nivolumab did not exhibit a similar effect. While CD8+ T cells alone showed near to no migration, adding CD4+ T cells enhanced migration towards the cancer cells. There was a mild nonsignificant increase in apoptosis of HSC-3 cells after adding epacadostat to lymphocytes. In contrast, HSC-3 proliferation was not affected by lymphocytes regardless of ICIs. Nivolumab significantly increased release of MIP1-α, IL-6, and IL-8 from NK, CD4+, and CD8+ T cells, respectively. Conclusions: This study revealed that each subpopulation of lymphocytes respond differently to ICIs. We also revealed the subpopulation of lymphocytes responsible for the increases in specific serum cytokines after ICI treatment.